2008
DOI: 10.1029/2007wr006268
|View full text |Cite
|
Sign up to set email alerts
|

Regional methods for trend detection: Assessing field significance and regional consistency

Abstract: [1] This paper describes regional methods for assessing field significance and regional consistency for trend detection in hydrological extremes. Four procedures for assessing field significance are compared on the basis of Monte Carlo simulations. Then three regional tests, based on a regional variable, on the regional average Mann-Kendall test, and a new semiparametric approach, are tested. The latter was found to be the most adequate to detect consistent changes within homogeneous hydro-climatic regions. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 43 publications
(80 reference statements)
5
133
0
7
Order By: Relevance
“…the p values themselves. An alternative method is based on the false discovery rate (FDR), which is the expected proportion of falsely rejected null hypotheses from the set of local tests (Renard et al 2008;Wilks 2006;Ventura et al 2004). The FDR can be controlled at a global significance level (α = 0.05) and a FDR probability is defined for each p value in the set of K ordered p values,…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the p values themselves. An alternative method is based on the false discovery rate (FDR), which is the expected proportion of falsely rejected null hypotheses from the set of local tests (Renard et al 2008;Wilks 2006;Ventura et al 2004). The FDR can be controlled at a global significance level (α = 0.05) and a FDR probability is defined for each p value in the set of K ordered p values,…”
Section: Methodsmentioning
confidence: 99%
“…Field significance is declared at the α significance level if at least one local null hypothesis has a p-value less than the P FDF and is thus rejected at the global significance level (Renard et al 2008;Wilks 2006). The FDR method assumes that all tests are independent, which is generally not true for spatial climate data, but Wilks (2006) showed that the method is robust to spatial dependence (Renard We evaluate the influence of spectral nudging by concatenating two simulations that differ only in their nesting strategy, CanRCM4_0.44 (uses spectral nudging) and Can-RCM4_NS (no spectral nudging).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies dealing with climate-driven changes for rivers in Europe covering countries like Germany, Swiss Alps, France, Spain and the United Kingdom have been reported in the literature [36][37][38][39] , but no trends have been found in flood magnitude and frequency on continental scale. Jiang et al 40 found increasing trend in annual maximum floods in the lower Yangtze River for the 40 years of data studied.…”
Section: Observed Changes In High Flows In Riversmentioning
confidence: 99%
“…The RAMK test indicates that trends are 25 statistically positive for 15-, 30-, and 1440-minute durations. The lack of a clear signal in the direction of the trends has been previously reported for other regions (Sarhadi and Soulis, 2017) and might be linked to the weak power of statistical methods when the data are affected by high natural variability as is the case of precipitation (Renard et al, 2008).…”
Section: Trend Analysis Of Precipitation Extremesmentioning
confidence: 93%
“…For both extreme value models, the magnitudes of the trends observed in the study period are assumed to continue at the same rate in the next 100 years into the future. Estimated precipitation intensities (return levels) for different return periods, and the corresponding credibility interval (this term is 20 called confidence interval in Frequentist context (Renard et al, 2008)) are shown in Fig. 5.…”
Section: Design Storms and Risk Under Stationary And Non-stationary Cmentioning
confidence: 99%